The Effect of STEM-Based Worksheet on Students’ Science Literacy - Sulistiyowati, Sulistiyowati; Abdurrahman, Abdurrahman; Jalmo, Tri (Universitas Islam Negeri Raden Intan Lampung, 2018)
This study aims to improve the students’ science literacy through the application of STEM-Based Worksheet (Science, Technology, Engineering, and Mathematics) on sound waves learning the material. The research used mixed-method with exploratory sequential design in the Nonequivalent Control Group Design. Samples were taken using purposive sampling technique. This study involved 25 eighth grade students of class F as the experimental class and 25 eighth grade students of class A as the control class in SMP Negeri 2 Pugung. The data collecting techniques were observation method, questionnaire, and test. The data were analyzed using independent sample t-test to see the effectiveness of the learning in both groups. The questionnaire results were analyzed descriptively. The results showed that the application of STEM-based worksheet could effectively increase the science literacy with N-gain of 0.43 (medium category). The highest increase was in the indicator of “explains the science phenomenon